Study guides

Q: What is the answer 2x2 plus 7x plus 3?

Write your answer...

Submit

Related questions

(2x + 1)(x + 3)

2x2 + 7x - 15 = (2x - 3)(x + 5)

(2x + 1)(x + 3) are the factors.

2x2-7x+3 = 0 (2x-1)(x-3) = 0 x = 1/2 or x = 3

You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

(2x + 1)(x + 3) = 0; x = -0.5 or -3

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

x2+7x=-2x2+6 3x2+7x-6=0 (3x-2)(x+3)=0 3x-2=0 or x+3=0 x=2/3 or x=-3

7x(3x3 - 2x2 + 5x + 1)

The factorisation is as follows: 2x2 + 7x - 9 = (x - 1)(2x + 9).

It is: 2x2-7x+6 = (2x-3)(x-2) when factored

2x2 - 7x + 3 2x2 = (2x)(x) Since the coefficient of x is negative (-7), then 3 = (-1)(-3). Therefore, 2x2 - 7x + 3 = (2x - 1)(x - 3)

2x^2+7x+5=(2x+5)(x+1)

Minus 61 (-61)

7x(3x3 - 2x2 + 5x + 1)

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

2x4 - 7x3 + x2 + 7x - 3 = (x + 1)(2x3 - 9x2 + 10x - 3) = (x + 1)(x - 1)(2x2 -7x + 3) = (x + 1)(x - 1)(x - 3)(2x -1)

2x + 3=7x

(x - 5)(2x + 3)

3x+7x+3+y= 10x+3+y

2 x 2 = 47 x 3 = 21

-6

2x2 + 7x - 15 = 02x2 + 10x - 3x - 15 = 0(2x2 - 3x) + (10x - 15) = 0x(2x - 3) + 5(2x - 3) = 0(2x - 3)(x + 5) = 0(2x - 3) = 0 or (x + 5) = 0x = 3/2 or x = -5

The answer to the math problem -3 7x plus 7 is x equals 1/3.